Sensitivity analysis of stormpav composite pavement - E. E., Putri; F. J. H., Rewani; Mohammad Abdul, Mannan; Wan Hashim, Bin Wan Ibrahim; Mohamad Raduan, Hj. Kabit; Larry, Anak Silas Tirau; Ron Aldrino, Chan@Ron Buking (IOP Publishing, 2019)
This study investigates the design and performance of modified composite pavement called StormPav. In this study, the sensitivity analysis is carried out by using available freeware to prove whether the StormPav composite pavement is able to provide long-life pavement and better levels of performance, both structural and functionally, than the traditional pavements. For this case, the sensitivity analysis is included data for fatigue behavior, rutting in the HMA (Hot Mix Asphalt) layer, and temperature gradient reduction of PCC slab with an HMA overlay. The StormPav composite pavement is actually an innovation IBS green pavement with structural, environmental and economic advantages. Inspired from Legos concept, the StormPav is made out of modular panels or "roadblocks" that are like enormous lego pieces that assemble and interlocking together forming a uniform settlement and at the same time acting as the monolithic character. The idea of StormPav is actually to minimize the usage of material in the composite pavement but provide the same strength and benefits as composite pavement.